Variasi Waktu Pengadukan dan Rasio Poly Aluminium Chloride (PAC) Terhadap Pengolahan Limbah Cair Industri Tahu - Cahyo, Ari Dwi; Riyanto, Andi; Rukmana, Mutiara Dewi; Putri, Silvia Devi Eka; Adriansyah, Endi; Suzana, Asih; Sufra, Rifqi (Universitas Batanghari Jambi, 2025)
Liquid waste from the tofu industry contains various organic and inorganic substances which can reduce water quality. This research aims to assess the effectiveness of Poly Aluminum Chloride (PAC) as a coagulant in reducing pollution parameters in liquid waste from the tofu industry. In this study, experiments were carried out with three variations of PAC doses (75 mg/L, 150 mg/L, and 225 mg/L) and different stirring times (10, 15, and 20 minutes) using the jar test method. The jar test method is a standard laboratory technique used to determine the optimal dose of coagulant needed to remove turbidity from wastewater. The results show that a PAC dose of 225 mg/L with a stirring time of 20 minutes is the optimal condition, reducing Total Dissolved Solids (TDS) from 996 ppm to significantly lower. The initial conductivity of 1971 µs decreased after the addition of high doses of PAC and longer stirring times. The pH parameter increased from 4 to 5. Although still acidic, this increase indicates a reduction in acidity, which can be useful in reducing negative impacts on the aquatic environment. The color of the wastewater becomes clearer and the odor decreases, indicating a decrease in organic compounds and dissolved substances. The temperature remained stable at 28ºC before and after treatment. This research confirms that PAC is effective in improving the quality of wastewater from the tofu industry through the coagulation mechanism, producing cleaner and clearer water with a significant reduction.